Marsa Matruh. the University of Pennsylvania Museum of Archaeology and Antrhopology's excavations on Bate's Island, Marsa Matruh, Egypt 1985-1989. - White, Donald, 1935-2018 (Prehistory monographs, 2002)
This volume of the report on the excavations at Marsa Matruh on Bates's Island, which is located on the seacoast at the north of Egypt's western desert, publishes the local and imported pottery, the crucibles and other evidence for metalworking, the organic finds (including ostrich egg shells), and the other discoveries made at the site. The pottery found in the excavations indicates that this small Late Bronze Age settlement had links to several cultures: Cyprus, the Aegean, Egypt, the coast of western Asia, and the local Marmarican people.